Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2011)
The current issue of Studies in Second Language Learning and Teaching brings together six contributions written by scholars from Poland and abroad which deal with a wide array of issues related to learning and teaching additional languages in different educational contexts. First, Weronika Szubko-Sitarek reports the findings of two experimental studies conducted within the lexical decision task paradigm which aimed to investigate the cognate facilitation effect in the process of recognizing words in a third language by Polish unbalanced trilinguals who, in addition to their mother tongue, were proficient in English and had variable command of German. In the next paper, Sane M. Yagi and Saleh Al-Salman make a strong case for the use of tracking software in writing pedagogy as a tool for providing invaluable insights into the process of composing texts, but also a method of stimulating reflection and promoting strategic learning. The research-based contributions by Ewa Waniek-Klimczak and Aleksandra Wach, in turn, shift the emphasis to sociolinguistic issues. The former presents the findings of a qualitative study which examined the acculturation patterns of three recent Polish immigrants to the United Kingdom, who were expert users of English, in relation to their formal and informal language learning experiences, while the latter uses questionnaire data obtained from a respectable sample of Polish-speaking English majors to shed light on their preferences concerning pronunciation norms based on the native-speaker model and the Lingua Franca Core. The last two papers included in this issue report the findings of studies exploring the role of anxiety in learning foreign language skills and subsystems. In the first of these, Christina Gkonou examines the interfaces between speaking and writing anxiety manifested by Greek learners of English as a foreign language in a private school setting and, in the second, Magdalena Szyszka taps the relationship between the level of anxiety of Polish advanced learners studying English in a teacher-training college and their self-evaluation of the segmental and suprasegmental aspects of their pronunciation. I believe that the broad range of issues tackled in the individual contributions, the diversity of the theoretical perspectives and research paradigms adopted, and the valuable pedagogical implications offered will all make this issue of SSLLT an engaging and stimulating reading for a variety of audiences.